Associations of spatial mobility with sexual risk behaviors among young men who have sex with men in New York City: A global positioning system (GPS) study. (August 2020) - Kim, Byoungjun; Regan, Seann D.; Callander, Denton; Goedel, William C.; Chaix, Basile; Duncan, Dustin T.
Abstract: Spatial contexts and spatial mobility are important factors of the HIV epidemic and sexually transmitted infections. Using global positioning system (GPS) devices, we examined the associations of objectively measured spatial mobility with sexual risk behaviors among gay, bisexual and other men who have sex with men (MSM) in New York City. This observational study included a subgroup of 253 HIV-negative MSM from the Project 18 Cohort Study, who participated in the GPS monitoring sub-study. Spatial mobility was measured as (1) distance traveled and (2) activity space size defined as daily path area during 2-week of GPS tracking. We examined the associations of these measures with numbers of male sexual partners and condomless anal intercourse (CAI) acts during last six months using quasi-Poisson models, adjusting for socio-demographics. Results demonstrated that spatial mobility was positively associated with sexual risk behaviors, for example, with CAI (incidence rate ratio [IRR] = 1.01 for a 10 km increase in distance traveled and IRR = 1.04 for a 1 km 2 increase in 50 m-buffer activity space size). Our findings may enhance the understanding of spatial contexts of HIV risk. Future studies should be conducted to examine the mechanisms for the associations between spatial mobility behaviors with sexual risk behaviors as well as the influence of neighborhood characteristics in various neighborhood contexts, which may guide the place-based HIV prevention services. Highlights: GPS-based spatial mobility was positively associated with sexual risk behaviors. Findings confirm the spatial contexts of HIV risks in urban environments. Future studies may guide the place-based HIV prevention services.